The Protective Role of Early Prosocial Behaviours Against Young Turkish Children's Later Internalizing and Externalizing Problems. Issue 3 (4th May 2022) - Gülseven, Zehra; Carlo, Gustavo; Kumru, Asiye; Sayıl, Melike; Selçuk, Bilge
ABSTRACT: This study examined the protective roles of early prosocial behaviours (at age 4) on later internalizing and externalizing problems (at age 6) and to what extent emotion regulation skills (at age 5) mediated these longitudinal associations in children from Turkey.  Participants were 293 Turkish preschool children ( M age  = 49.01 months; 141 girls). Results showed that higher prosocial behaviours at age 4 were linked to higher emotion regulation at age 5, which, in turn, was linked to less internalizing problems at age 6. Additionally, prosocial behaviours at age 4 were negatively linked to emotional lability at age 5, which, in turn, was positively linked to externalizing problems at age 6. We also found that higher prosocial behaviours at age 4 were directly and negatively linked to both internalizing and externalizing problems at age 6. These results were robust for boys and girls and children who lived in big and small cities. Overall, there was supportive evidence on the protective roles of earlier prosocial behaviours on later internalizing and externalizing problems. These findings extend existing models of risk and resilience to a sample of children from a non-Western, relatively collectivist-oriented culture and inform our understanding of these posited relations in young children.